THE CONFIDENCE WITH ANXIETY AS A PRESENTATION IN THE CLASS OF NURSING STUDENTS AT THE UNIVERSITY OF MUHAMMADIYAH TANGERANG - Shieva Nur Azizah Ahmad; Aprilia Ratnasari (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2020)
The anxiety of speaking in front of the class is one of the greatest fears experienced by every human being. Speaking anxiety experienced by someone when making a presentation in front of the class due to lack of self-confidence. This study aims to determine the relationship of confidence with anxiety when making presentations in class at nursing students at the University of Muhammadiyah Tangerang. This research method uses quantitative research with cross sectional design. The population in this study amounted to 78 nursing students. Samples taken in this study used Non Probability Sampling with Purposive Sampling techniques in accordance with the inclusion and exclusion criteria in the study. Data were analyzed with Chi Square test. The results of this study there is a relationship of confidence with anxiety when making presentations in class of nursing students in 2nd semester at the University of Muhammadiyah Tangerang with P Value (0.039) <Alpha (0.05). This research is expected to increase students' confidence when making presentations in class by extending exercises such as practicing speaking in front of the class.